2003
DOI: 10.1242/jeb.00105
|View full text |Cite
|
Sign up to set email alerts
|

PPNDS is an agonist, not an antagonist, for the ATP receptor of Paramecium

Abstract: SUMMARY Paramecium represents a simple, eukaryotic model system to study the cellular effects of some neuroactive drugs. They respond to the agonistβ,γ-methylene ATP with a transient depolarizing receptor potential,Ca2+-based action potentials and repetitive bouts of forward and backward swimming called `avoiding reactions' (AR). In vivo[32P]ATP binding assays showed saturable [32P]ATP binding with an apparent Kd of approximately 23 nmol l-1. Prolonged (15 min) exposure to 25 μmol l-1β,γ-methyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Inspection of the crystal structures showed that 6 binds to a site located in the polymerase thumb domain, more specifically in a cleft along the exit path for the newly synthesized RNA. This site doesn't match the previously identified Suramin binding site, but corresponds to the Pyridoxal-5′-phosphate-6-(2′-naphthylazo-6′-nitro-4′,8′-disulphonate; PPNDS) [32], [33] binding site [34](Tarantino et al in press). Notably, PPNDS is also a molecule composed of two parts: the naphthalene disulphonate head and the pyridoxal phosphate group, linked by an azo bridge.…”
Section: Discussionmentioning
confidence: 91%
“…Inspection of the crystal structures showed that 6 binds to a site located in the polymerase thumb domain, more specifically in a cleft along the exit path for the newly synthesized RNA. This site doesn't match the previously identified Suramin binding site, but corresponds to the Pyridoxal-5′-phosphate-6-(2′-naphthylazo-6′-nitro-4′,8′-disulphonate; PPNDS) [32], [33] binding site [34](Tarantino et al in press). Notably, PPNDS is also a molecule composed of two parts: the naphthalene disulphonate head and the pyridoxal phosphate group, linked by an azo bridge.…”
Section: Discussionmentioning
confidence: 91%
“…The naphthylazo derivative of the PPADS family, PPNDS, inhibits rP2X1R at nanomolar concentrations, with an IC 50 of 15 nM (Lambrecht et al, 2000b) but behaves as an agonist for the ATP receptor in Paramecium spp. (Wood and Hennessey, 2003). Two other PPADS derivatives, MRS2159 and MRS2220, are highly selective for ATP-induced responses in rP2X1R, and are ectonucleotidase resistant (Jacobson et al, 1998;Kim et al, 2001).…”
Section: Activation and Regulation Of P2xrsmentioning
confidence: 99%
“…From this, the occurrence of surface receptors for GTP has been inferred in Paramecium [25][26][27] and Tetrahymena [23,28,29]. The typical receptor property, i.e., adaptation [30,31], has also been observed with GTP in Paramecium [25] and Tetrahymena [23].…”
Section: Introductionmentioning
confidence: 83%
“…The fact that GTP causes the phenomena described, while ATP or UTP do not [26], remains undisputed, although non-hydrolysable ATP analogues work equally well at very low concentrations [27]. Binding studies strongly suggest the occurrence of purinergic receptors in Paramecium [27] and Tetrahymena [29].…”
Section: Are There Purinergic Surface Receptors In Paramecium and Whamentioning
confidence: 92%
See 1 more Smart Citation